Strategies for flexibility: technology-centred and labour-centred flexibility in UK manufacturing. (1st January 2000) - Procter, Stephen; Ackroyd, Stephen
This paper examines the form in which British manufacturing industry has assumed greater flexibility. Two basic types of flexibility are identified: technology-centred and labour-centred. Each of these has generated a substantial literature of its own; each, however, gives little consideration to the other. To the extent they have been considered together, the assumption has been that flexible manufacturing technologies require multi-skilled labour. The argument presented in this paper is that flexibility in technology and flexibility in labour should be regarded not as complementary but as substitutes for each other. Evidence from British industry shows that the use of advanced manufacturing technology is not widespread and that, where it is used, its potential benefits are not fully exploited; other evidence shows labour flexibility to have been pursued systematically. Analysis of firms' strategies will take into account the fact that the conditions under which they operate will make certain courses of action more likely to be taken than others. A number of reasons have been advanced as explanations of British manufacturing's low and poor use of advanced manufacturing technology. It is these same conditions that make the pursuit of an exploitative form of labour flexibility the more attractive alternative.